THE EFFECT OF TAX FAIRNESS, TAX KNOWLEDGE, AND TAX COMPLEXITY ON TAX COMPLIANCE: THE CASE OF SME ENTREPRENEURS’ TAXPAYERS IN MALANG - Mariah Qibthiyyah Brainyyah; M. Khoiru Rusydi (Jurnal Ilmiah Mahasiswa FEB, 2012)
Tax contribution is very important for the organization of a Country beside other revenues such as natural resources, profits of state-owned enterprises, fees, and other revenue sources. It can be said that taxes revenue is worth the largest domestic revenue. Without tax compliance from the taxpayers, tax revenue target would not be reached. There are economical and non-economical factors which are possible to influence the tax compliance. However, this study aims to determine and ensure the effect of perceived tax fairness, tax knowledge, and tax complexity in tax compliance decisions among SME entrepreneurs in Malang. To test the model, a questionnaire consisted questions related to the three variables and one dependent variable which is tax compliance was administered among 32 samples of SME entrepreneurs in Malang. The data was then analyzed by multiple regression method which was undertaken with SPSS 15.0 software. The findings revealed that simultaneously, perceived tax fairness, tax knowledge and tax complexity influence taxpayers’ compliance decision in order to meet their taxation obligations. While the partial test showed that both tax fairness and tax complexity affect the tax compliance among SMEs taxpayers in Malang while the tax knowledge did not give any significant effect on tax compliance.   Keyword: tax fairness, tax knowledge, tax complexity, tax compliance